2012
DOI: 10.1177/1532673x11432470
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Election Day Registration on Voter Turnout and Election Outcomes

Abstract: Voter registration is widely viewed as a barrier to voter participation in general, and especially so for likely Democratic voters. A popular remedy for both turnout effects is election day registration (EDR), which eliminates the closing date by permitting registration at the polls. Following earlier research we posit a small positive effect of EDR on turnout. But contrary to conventional wisdom, we theorize that individuals most likely to take advantage of EDR are in fact Republican voters. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…36 In other words, in terms of net mobilization, preregistration appears to slightly advantage Republicans. This pattern is quite consistent with previous studies that have found institutional programs tend to register more Democrats (Herron and Smith 2012) but mobilize more Republicans (Cain and McCue 1985;Neiheisel and Burden 2012).…”
supporting
confidence: 82%
“…36 In other words, in terms of net mobilization, preregistration appears to slightly advantage Republicans. This pattern is quite consistent with previous studies that have found institutional programs tend to register more Democrats (Herron and Smith 2012) but mobilize more Republicans (Cain and McCue 1985;Neiheisel and Burden 2012).…”
supporting
confidence: 82%
“…Recent research argues that election laws are endogenous to political participation (Erikson and Minnite ; Hanmer ), either due to simultaneity (i.e., reforms result as responses to turnout) or to complex, not well‐understood networks of unobserved variables (e.g., motivation). For example, quasi‐experimental studies of the impact of Election Day registration have shown marked differences to observational studies on the same topic (Keele and Minozzi ; Neiheisel and Burden ).…”
Section: Introductionmentioning
confidence: 99%
“…Even within federal constraints, there remains considerable variation across states in the ease of voter registration. Political scientists have long debated the extent to which voter turnout might be fostered or hindered by various electoral rules, such as registration windows (Brians and Grofman ; Hanmer ; Keele and Minozzi ; Leighley and Nagler ; Neiheisel and Burden ), voter identification restrictions (Alvarez, Bailey and Katz ; Atkeson et al. ; Erikson and Minnite ; Mycoff, Wagner and Wilson ; Vercellotti and Anderson 2010), or online registration tools (Bennion and Nickerson ; Hanmer et al.…”
mentioning
confidence: 99%
“…While higher turnout in the South after the collapse of the New Deal coalition was later shown to benefit Democrats, evidence suggests that the end of black disenfranchisement in the 1960s is responsible rather than a broadly applicable turnout-partisan dynamic (see Erikson 1995). Regional trends notwithstanding, most recent research has supported DeNardos conclusion that Democrats do not necessarily benefit from higher turnout (Citrin, Schickler, and Sides 2003;Franklin and Grier 1997;Hanmer 2007Hanmer , 2009Highton and Wolfinger 2001;Neiheisel and Burden 2012).…”
Section: The Partisan Effects Of Turnoutmentioning
confidence: 99%